The Roman Inquisition on the Stage of Italy, c. 1590-1640 - Mayer, Thomas F. (Thomas Frederick), 1951-2014 (Book collections on Project MUSE., 2014)
Drawing on the Roman Inquisition's own records, diplomatic correspondence, local documents, newsletters, and other sources, Thomas F. Mayer provides an intricately detailed account of the ways the Inquisition operated to serve the papacy's long-standing political aims in Naples, Venice, and Florence between 1590 and 1640.